Antioxidant, Transcriptome and the Metabolome Response to Dietary Astaxanthin in Exopalaemon carinicauda - Li, Wenyang; Wang, Jiajia; Li, Jitao; Liu, Ping; Li, Jian; Zhao, Fazhen (Frontiers in Physiology, 2022)
Astaxanthin (Axn), a feed additive, is becoming increasingly important for modulating the metabolism, growth, development, and reproduction of aquatic organisms in aquaculture. In this study, Exopalaemon carinicauda (E. carinicauda) is an economically important fishery species in China that has been found to exhibit increased body weight following Axn feeding as compared to a standard diet. The antioxidant, transcriptomic, and metabolomic analyses of the response of E. carinicauda after Axn feeding were investigated. Axn could reduce the content of malondialdehyde and increase the activities of various antioxidant enzymes, which also proved that axn can improve the antioxidant capacity Transcriptomic analysis suggested that synthesis and secretion of immune proteins, cytoskeleton structure, and apoptosis signaling were altered after Axn feeding. The metabolic response to axn mainly includes the up regulation of different amino acids and the change of unsaturated fatty acids. Combined transcriptomic and metabolomic data indicated that amino acid metabolic pathways were upregulated in the muscles after Axn feeding. For good measure, energy metabolism pathways were upregulated in the muscles to improve ATP and unsaturated fatty acid production. This study provides key information to increase our understanding of the effects of Axn in shrimp.